2014
DOI: 10.1113/jphysiol.2014.279950
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin C and E supplementation alters protein signalling after a strength training session, but not muscle growth during 10 weeks of training

Abstract: Key pointsr Although antioxidant supplements are generally believed to give health benefits, recent experiments show that they may adversely affect adaptations to endurance exercise.r This study is the first to investigate the effects of high dosages of vitamins C and E on the cellular and physiological adaptations to strength training in humans.r Here we report that vitamin C and E supplementation interfered with exercise-induced signalling in muscle cells after a session of strength training, by reducing the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
124
3
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 124 publications
(133 citation statements)
references
References 55 publications
4
124
3
2
Order By: Relevance
“…Despite an increase in muscle mass over 10 weeks of training, we have reported that vitamin C and E supplementation blunted hypertrophy related signaling to the strength training session investigated in the present study [25]. Based on these results, we hypothesized that vitamin C and E supplementation would be able to blunt the stress induced by exercise, measured as reduced activation of NFκB pathway, and expression of HSPs (CRYAB and HSPB1) or antioxidant enzymes (SOD2 and GPx1).…”
Section: Introductionmentioning
confidence: 73%
See 2 more Smart Citations
“…Despite an increase in muscle mass over 10 weeks of training, we have reported that vitamin C and E supplementation blunted hypertrophy related signaling to the strength training session investigated in the present study [25]. Based on these results, we hypothesized that vitamin C and E supplementation would be able to blunt the stress induced by exercise, measured as reduced activation of NFκB pathway, and expression of HSPs (CRYAB and HSPB1) or antioxidant enzymes (SOD2 and GPx1).…”
Section: Introductionmentioning
confidence: 73%
“…Contrary to our initial hypothesis, vitamin C and E supplementation did not blunt the IκBα response or the concomitant changes in HSP (CRYAB and HSPB1) and endogenous antioxidant (SOD2 and GPx1) mRNA levels in response to a session of heavyload strength exercise. Despite an increase in muscle strength and mass in upper-and lower body exercises in both groups [25], no changes were observed in protein levels in the investigated HSPs (αB-crystallin, HSP27 or HSP70) or endogenous antioxidants (GPx1 and mnSOD) after 10 weeks of heavy load strength training.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In terms of a supplemental dose, the EFSA have recently stated that 4000iU is the maximum dose that should be used which we have also shown to be an effective dose in correcting deficiencies [146]. Recent work from our group [147] This is best exemplified by the notion that decreasing reactive oxygen species (ROS) generation with nutritional antioxidants, attenuates exercise-induced redox signalling, and thereby blunts exercise adaptation [150,151]. Over the last decade research has therefore somewhat switched focus from looking at exercise-induced ROS generation as being damaging at all times with nutrition focused on prevent any increase in ROS production…”
Section: Beta-alanine More Recently Muscle Concentrations Of the DImentioning
confidence: 99%
“…Initially, RNOS were thought to be detrimental to athlete recovery, but it is now clear that RNOS are important for adaptation to endurance training (Finaud et al 2006, Ristow et al 2009, Powers et al 2010a, skeletal muscle hypertrophy and protein signaling (Makanae et al 2013, Paulsen et al 2014). Nonetheless, a critical balance (captured in the theory of hormesis; Radak et al, (2008) exists between the sufficient or "optimal" dose of RNOS to drive adaptation, and the overproduction of RNOS that could lead to apoptosis, immunosuppression, excessive fatigue and reduced performance (Levada-Pires et al 2008, Lewis et al 2015 The monitoring of elite athletes is widespread with considerable resources devoted to improving performance (Davison et al 2009).…”
Section: Introductionmentioning
confidence: 99%